2022
DOI: 10.1101/2022.04.21.489034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DiffBrainNet: differential analyses add new insights into the response to glucocorticoids at the level of genes, networks and brain regions

Abstract: Genome-wide gene expression analyses are invaluable tools for increasing our knowledge of biological and disease processes, allowing a hypothesis-free comparison of gene expression profiles across experimental groups, tissues and cell types. Traditionally, transcriptomic data analysis has focused on gene-level effects found by differential expression. In recent years, network analysis has emerged as an important additional level of investigation, providing information on molecular connectivity, especially for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…This suggests that other stress-induced signals can also regulate these genes more slowly or with a greater delay. Indeed, a recent study reported that activation of the glucocorticoid receptor by dexamethasone can induce strong transcriptomic changes 4 hours after injection across multiple brain regions (Gerstner et al 2022) . Analyzing their data we found that Dio2 , Ppp1r3c and Ppp1r3g were all upregulated 4 hours after dexamethasone injection.…”
Section: Complex Interactions Between Stress Mediatorsmentioning
confidence: 99%
“…This suggests that other stress-induced signals can also regulate these genes more slowly or with a greater delay. Indeed, a recent study reported that activation of the glucocorticoid receptor by dexamethasone can induce strong transcriptomic changes 4 hours after injection across multiple brain regions (Gerstner et al 2022) . Analyzing their data we found that Dio2 , Ppp1r3c and Ppp1r3g were all upregulated 4 hours after dexamethasone injection.…”
Section: Complex Interactions Between Stress Mediatorsmentioning
confidence: 99%
“…This suggests that other stress-induced signals can also regulate these genes more slowly or with a greater delay. Indeed, a recent study reported that activation of the glucocorticoid receptor by dexamethasone can induce strong transcriptomic changes 4 hr after injection across multiple brain regions ( Gerstner et al, 2022 ). Analyzing their data we found that Dio2 , Ppp1r3c, and Ppp1r3g were all upregulated 4 hr after dexamethasone injection.…”
Section: Discussionmentioning
confidence: 99%